E2.4 Praise – promoting appreciative inquiry, supporting excellence. (4th October 2017) - Sidgwick, P; Thankaraj, Simi; Hothi, Dal; Rees, Clare
Abstract : background: Praise is a QI project that seeks to identify excellence within the daily practice of all sectors of great ormond street hospital staff through peer reporting. Methods: Design of a simple intranet-based form followed by soft-launch (five emails and one mdt meeting presentation) to all members of theatre, anaesthetic, radiology and intensive care teams. all forms analysed against relevant trust values and thematic analysis performed to derive master themes from peer feedback. all staff making or receiving a praise received a written record of this and were invited to an appreciative inquiry event. Results: 62 praise forms were completed within the first 12 weeks of the programme. the flow of praise is represented in figure 1, with each arrow representing one praise episode. The majority of praisers were medical (67%) whilst praisees were split equally between medical and nursing/allied health professionals (38% and 32% respectively) with the remainder between non-clinical staff such as cleaners and administrative staff. 12 (19%) directly praised actions which impacted positively upon patient care and 29 (46%) praised general brilliance. the gosh values 'always helpful' and 'always one team' were the most frequently cited (63%) trust values by praisers. 28 (45%) praise forms were from senior team members praising more junior team members; 7 (11%) were from junior to senior team members. Conclusion: This pilot of praise within a small number of departments within great ormond street has demonstrated a clear appetite for a system that allows peers to report excellence across all fields of the trust's reach. there is rich learning to be gained from appreciative inquiry and thematic analysis of the practices and data that this programme showcases.